2021
DOI: 10.4081/oncol.2021.547
|View full text |Cite
|
Sign up to set email alerts
|

The effect of imatinib and nilotinib on blood calcium and blood potassium levels in chronic myeloid leukemia patient: a literature review

Abstract: Imatinib and nilotinib are first-line treatments for chronic myeloid leukemia (CML) patients, which act specifically against target cells. However, these drugs may cause side effects, such as electrolyte disturbances. This literature review aimed to provide a comparison of the effects of imatinib and nilotinib on blood potassium and calcium levels. It also summarized their hypothetical mechanism. A comprehensive electronic search of the different databases was conducted using "chronic myeloid leukemia”, “tyros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…29 A previous study indicated that Imatinib and Nilotinib acted on both the BCR-ABL1 gene and the platelet derived growth factor which may cause kidney disorders and affect blood potassium levels. 36 A retrospective study by Marcolino et al, (2011), included 100 CML in chronic phase (CML-CP) patients, and another study by Yilmaz et al, (2015) included 253 patients with CML-CP treated with Imatinib, reported that the patient's blood potassium level was not increased. 37,38 In China, a study by Wang et al, (2015) reported that the decrease in blood potassium levels of all grades was more prevalent in CML-CP patients treated with Imatinib (50%) compared to Nilotinib (21.1%).…”
Section: Discussionmentioning
confidence: 99%
“…29 A previous study indicated that Imatinib and Nilotinib acted on both the BCR-ABL1 gene and the platelet derived growth factor which may cause kidney disorders and affect blood potassium levels. 36 A retrospective study by Marcolino et al, (2011), included 100 CML in chronic phase (CML-CP) patients, and another study by Yilmaz et al, (2015) included 253 patients with CML-CP treated with Imatinib, reported that the patient's blood potassium level was not increased. 37,38 In China, a study by Wang et al, (2015) reported that the decrease in blood potassium levels of all grades was more prevalent in CML-CP patients treated with Imatinib (50%) compared to Nilotinib (21.1%).…”
Section: Discussionmentioning
confidence: 99%
“…Variants in either the alpha or beta PDGFR might be an important area to investigate relative to electrolyte imbalances that occur in some patients, as a review by Prenggono et al concluded [38]. They observed that blood calcium and potassium levels tend to decrease in some patients treated with imatinib and postulated that, for potassium, this could be due to the role played by the PDGFR in kidney physiology, where it is needed for renal tubular regeneration.…”
Section: Additional Considerations Impacting Patient Responsementioning
confidence: 99%
“…The story of hypocalcemia is less clear. Calcium levels in patients taking imatinib range from the lower normal values to hypocalcemia but no clear explanation for this has been established [38]. These trends may be of particular importance in patients who already suffer from renal and/or cardiac issues.…”
Section: Additional Considerations Impacting Patient Responsementioning
confidence: 99%
See 1 more Smart Citation